Influence of Heterometallic Hydroxycarboxylatogermanates/Stantates on Fibrinogenolitic Activity of Bacillus sp. IMV B-7883 - Gudzenko, O.V.; Varbanets, L.D.; Seifullina, I.I.; Martsynko, O.E.; Finik, O.A.; Гудзенко, O.В.; Варбанець, Л.Д.; Сейфулліна, I.Й.; Maрцинко, O.E.; Фінік, O.A. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Different ways can be used to increase the biosynthesis and activity of enzymes: changing the conditions for growing microorganisms, applying genetic manipulations, and also using various coordination compounds, in particular, heterometallic carboxylatogermanates/stannates. They represent a class of compounds with unique structural and functional properties. Due to their ability to form various coordination polymers and complexes with biomolecules, they can effectively influence the structure and function of enzymes. Earlier, we investigated the effect of some heterometallic carboxylatogermanates/stannates on the activity of Bacillus sp. IMV B-7883 elastase. The purpose of this work was to study the influence of these coordination compounds on the fibrinogenolytic activity of Bacillus sp. IMV B-7883. Methods. The object of the investigation was the strain of Bacillus sp. deposited in the Ukrainian Collection of Microorganisms under the number IMV B-7883, isolated from soil. The culture was grown under conditions of submerged cultivation at 28 °С, with a mixing speed of the nutrient medium of 244 rpm for 3 to 6 days (72–144 hours). We used an enzyme purified from the supernatant of the culture liquid by precipitation with 90% ammonium sulfate, with further fractionation on neutral and charged carriers. To determine fibrinogenolytic activity, fibrinogen was used as a substrate. As modifiers of enzyme activity, heterometallic carboxylatogermanates/stannates were used. Results. Of the 15 investigated coordination compounds, 3 turned out to be the most interesting. The compound [Ba(H2O)6][Ge2(OH)2(H2Gluc)2]×2H2O (H6Gluc – gluconic acid) in both tested concentrations at an exposure time of 1 h showed the greatest inhibitory effect (48%), as well as compound [Cu(H2O)6][Ge2(OH)2(H2Gluc)2]×4H2O inhibited to a lesser extent (40%) in both studied concentrations at an exposure time of 24 h. Along with that, the compound [Co(phen)3]2[{Sn(HMal)2(Mal)}Cl]×14H2O (Н3Mal – malic acid) activated the fibrinogenolytic activity of Bacillus sp. IMV B-7883 by 2.28 times. Conclusions. Modification of the Bacillus sp. IMV B-7883 enzyme with fibrinogenolytic activity by heterometallic hydroxycarboxylatogermanates/stannates is a p romising area of research. It opens up new opportunities for the creation of biocatalysts with unique properties.